2011
DOI: 10.1002/path.2947
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils promote motility of cancer cells via a hyaluronan‐mediated TLR4/PI3K activation loop

Abstract: Inflammation is a component of tumour progression mechanisms. Neutrophils are a common inflammatory infiltrate in many tumours, but their regulation and functions in neoplasia are not understood. We recently demonstrated that pro-inflammatory IL-17-producing cells recruited blood neutrophils into the peritumoural stroma of hepatocellular carcinoma by epithelium-derived CXC chemokines. Here we show that a substantial population of neutrophils accumulates in the peritumoural stroma of hepatocellular, cervical, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 123 publications
(98 citation statements)
references
References 45 publications
2
94
1
Order By: Relevance
“…Changes in the staining patterns induced by radiotherapy (RT). an abundance of mast cells, in accordance with animal studies demonstrating an influx of mast cells during RT (33,34). There is an established correlation between chronic inflammation and cancer (35) and mast cells are known to contribute to pre-malignant progression (36)(37)(38)(39).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Changes in the staining patterns induced by radiotherapy (RT). an abundance of mast cells, in accordance with animal studies demonstrating an influx of mast cells during RT (33,34). There is an established correlation between chronic inflammation and cancer (35) and mast cells are known to contribute to pre-malignant progression (36)(37)(38)(39).…”
Section: Discussionsupporting
confidence: 61%
“…Irradiation is known to induce structural alterations of HA such as degradation (33) and cause alteration of the physical properties; however, to which extent, is yet unknown. HA fragments are further released by most solid tumour cells and activate inflammatory cell signalling, promoting tumour motility (34). In the present study, however, we did not detect any changes in HA expression in normal epithelium or in the one sample with viable tumour cells following RT.…”
Section: Discussioncontrasting
confidence: 53%
“…We previously showed that environmental hyaluronan (HA) fragments from hepatoma cells induced protumorigenic myeloid cells via TLR4 activation ( 23 ) . D, CD40L plus CpG ODN, anti-human IgM, or anti-IgM, IgA, and IgG cocktail used as combined stimuli triggered IL10 production in blood CD38 hi CD24 hi Bregs but not in CD5 hi CD27 hi/ + tumor B cells.…”
Section: Factors That Modulate Pd-1 Expression On B Cells In Hccmentioning
confidence: 99%
“…Proteins from cells were extracted as previously described ( 23 ). The antibodies used are listed in Supplementary Table S5.…”
Section: Immunoblottingmentioning
confidence: 99%
“…[14][15][16] Neutrophils are the most abundant leukocytes and serve as essential effector cells in the first line of host defense against invading microorganisms. 17,18 In addition to direct bactericidal activities, neutrophils can actively regulate angiogenesis and tissue remodeling by releasing multiple proteases.…”
Section: Introductionmentioning
confidence: 99%